Microbiology perspectives : a photographic survey of the microbial world - Wistreich, George (Upper Saddle River, New Jersey : Pearson Prentice Hall, 2007)
"[This book] provides a visual guide to many of the specific properties, activities and procedures associated with microorganisms and helminths (worms). It also discusses selected features of a number of infectious diseases. In short, this book is intended to present microorganisms to anyone who is interested and curious about the microbial world. Individuals, whether familiar or not familiar with this microscopic world of life, can gain some perspective as to the many types of microorganisms and their activities that exist in the world around them."--Preface, p. xvii. This extremely readable, well-illustrated, presentation covers a wide range of microorganisms and their activities. It presents photographs and data about organisms that are not normally found in laboratory manuals and often not found in textbooks. Readers learn the characteristics of various types of microorganisms, along with pertinent information about microorganism-caused disease (bacterial, fungal, protozoan, viral, helminthic). Updates and increases coverage of basic laboratory procedures and associated results, the domains of microbal life, immunology, and infectious diseases. Increased emphasis on the features of viruses and prions: discusses the use of selected agents of bioterrorism, and adds coverage on the SARS agent, Ebola and Marburg viruses, and the human metapneumovirus. Features new illustrations throughout that emphasize the variety of microorganisms and their activities, increasing the microbiology perspective. A laboratory supplement for students studying to be nurses, medical assistants, dental assistants, medical technologists. It may also be used in biology majors labs.
Modern imaging techniques -- Bacteriology -- Bacteriology : a survey of the bacteria and archeae domains -- Mycology -- Algology (protists--the algae) -- Protozoology (protists--the protozoa) -- Virology -- Helminthology -- Arthropods and disease -- Immunology.
Includes index.
Keywords: MICROBIOLOGY -- ATLASES